Is Mini-Plate Removal Necessary for Oral and Maxillofacial Surgery Patients? A Five-Year Case-Control Study - Mehdi Fani; Sahand Samieirad; Zahra Shooshtari; Maryam Jamali; Elahe Tohidi (Tehran University of Medical Sciences, 2020)
Objectives: The purpose of this study was to determine the mini-plate and screw removal rate and reasons in maxillofacial surgery patients under previous semi-rigid fixation treatment in the past five years at the main trauma center of Mashhad. Materials and Methods: This was a census-based retrospective study. All the candidates who admitted to our department for maxillofacial plate removal due to symptomatic or infected mini-plates were included in this study. The patients' age and gender, plate removal etiologies, and the time between plate insertion and removal were analyzed. Results: Mini-plates were inserted for 1026 patients. However, only 94 patients with a mean age of 29.4±11.1 years were candidates for plate removal. The plate removal rate was 9.16%. Infection and exposure were the most common causes of plate removal. The most prevalent removal site was the mandible (angle and body). The interval between mini-plate insertion and removal was an average of 12.9±5.6 months. It is noteworthy that the shortest lasting duration was when plate removal was secondary to pain (6.67 months) and infection (11.45 months). Conclusion: This research showed that the routine removal of plates does not appear to be generally indicated in healthy subjects unless there is an obvious and definitive clinical indication.